2016
DOI: 10.1111/nep.12586
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes of supportive care versus dialysis therapies for elderly patients with end‐stage kidney disease: A systematic review and meta‐analysis

Abstract: While the available literature demonstrates a broadly similar 1-year survival in elderly ESKD patients, it does not allow a confident estimate of the relative survival benefits of dialysis or supportive care. This uncertainty needs urgent attendance by further prospective data, which avoid bias and allow comparisons of quality of life and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 26 publications
(39 reference statements)
2
114
0
4
Order By: Relevance
“…Non-dialysis options may also be appropriate for patients whose goals and priorities are to focus on the quality of their life rather than treatments aimed to extend life. Although there are no prospective studies comparing survival with dialysis versus conservative management most studies and a recent meta-analysis showed similar survival [6770]. Patients who choose conservative therapy have relatively preserved functional status until the last months of life [67–69].…”
Section: Main Textmentioning
confidence: 99%
“…Non-dialysis options may also be appropriate for patients whose goals and priorities are to focus on the quality of their life rather than treatments aimed to extend life. Although there are no prospective studies comparing survival with dialysis versus conservative management most studies and a recent meta-analysis showed similar survival [6770]. Patients who choose conservative therapy have relatively preserved functional status until the last months of life [67–69].…”
Section: Main Textmentioning
confidence: 99%
“…Currently, in developed nations, the age cohort of dialysis patients that has the highest prevalence are 65–80 year olds . Multiple studies suggest that patients over 75 years with ESKD and significant comorbidities have a similar survivorship to their contemporaries who chose a non‐dialysis pathway . This fact and a recognition of the necessity of improved symptom management, advance care planning and care of the dying patient led to an evolving alliance between the disciplines.…”
Section: Palliative Care and Three Modern Phenomena In Modern Medicinementioning
confidence: 99%
“…Foote et al (16) reported that the annual survival of patients on hemodialysis or peritoneal dialysis was 73.0% (95% confidence interval, 66.3% to 79.7%) and that the annual survival of patients on conservative management was 70.6% (95% confidence interval, 63.3% to 78.0%), suggesting that the annual mortalities between treatment options were similar. The overall median survival advantage presented by Verberne et al (15), in contrast to results from the systematic review, may reflect differences in patient characteristics between studies and varying definitions in starting points of comparison.…”
mentioning
confidence: 99%